2016
DOI: 10.1021/acs.jafc.6b02649
|View full text |Cite
|
Sign up to set email alerts
|

Free and Protein-Bound Maillard Reaction Products in Beer: Method Development and a Survey of Different Beer Types

Abstract: The Maillard reaction is important for beer color and flavor, but little is known about the occurrence of individual glycated amino acids in beer. Therefore, seven Maillard reaction products (MRPs), namely, fructosyllysine, maltulosyllysine, pyrraline, formyline, maltosine, MG-H1, and argpyrimidine, were synthesized and quantitated in different types of beer (Pilsner, dark, bock, wheat, and nonalcoholic beers) by HPLC-ESI-MS/MS in the multiple reaction monitoring mode through application of the standard additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 49 publications
5
77
0
1
Order By: Relevance
“…Similarly, the bound form predominated over the free ones in dairy products by factors of 276 for CML and 11 for pyrraline, respectively (Hegele et al., 2008). By contrast, beer (free/bound pyrraline ratio = 2.6) and soy source (free/bound CML ratio >90) were shown to be more abundant in free AGEs, which is likely ascribed to proteolysis during fermentation (Hellwig, Witte, & Henle, 2016; Li et al., 2015). Considering the differential metabolic profiles of dAGEs with different MW, we would shortly conclude that future investigations discriminating between free and bound AGEs, including their health‐related influences and contents in processed foods, are particularly highlighted.…”
Section: Health Implications Of Dages: Perspectives To Fill the Gap Bmentioning
confidence: 99%
“…Similarly, the bound form predominated over the free ones in dairy products by factors of 276 for CML and 11 for pyrraline, respectively (Hegele et al., 2008). By contrast, beer (free/bound pyrraline ratio = 2.6) and soy source (free/bound CML ratio >90) were shown to be more abundant in free AGEs, which is likely ascribed to proteolysis during fermentation (Hellwig, Witte, & Henle, 2016; Li et al., 2015). Considering the differential metabolic profiles of dAGEs with different MW, we would shortly conclude that future investigations discriminating between free and bound AGEs, including their health‐related influences and contents in processed foods, are particularly highlighted.…”
Section: Health Implications Of Dages: Perspectives To Fill the Gap Bmentioning
confidence: 99%
“…One interesting work on Maillard Reaction Products (MRPs) present in beer was carried out by Hellwing et al 2016 [97]. They quantified seven MRPs in different types of beer (Pilsner, dark, bock, wheat, and nonalcoholic beers) by HPLC-ESI-MS/MS in the multiple reaction monitoring mode through application of the standard addition method ( Figure 6).…”
Section: Measurements Of Melanoidin Contentmentioning
confidence: 99%
“…Results concluded that the most important free MRPs in beer are fructosyllysine (6.8-27.0 mg/L) and maltulosyllysine (3.7-21.8 mg/L). In addition, the analyzed beers contained comparatively high amounts of late-stage free MRPs such as pyrraline (0.2-1.6 mg/L) and MG-H1 (0.3-2.5 mg/L) and minor amounts of formyline (4-230 µg/L), maltosine (6-56 µg/L), and argpyrimidine (0.1-4.1 µg/L) [97].…”
Section: Measurements Of Melanoidin Contentmentioning
confidence: 99%
“…These characteristics in dark malt are the result of a Maillard reaction (MR) that is initiated due to the killing temperatures used in the production of such malts [7]. The MR, also called non-enzymatic browning, is a network of chemical reactions that are initiated by the addition of reducing sugar to proteins, peptides, amino acids or amines, to form an Amadori rearrangement product (ARP) [8,9]. The formation of flavour compounds in the MRs depends on the type of sugars and amino acids involved, as well as on the reaction temperature, time, pH and water content.…”
Section: Maillard Reactionmentioning
confidence: 99%
“…In the final stage, dehydration, fragmentation, cyclization and polymerisation reactions occur, which amino group participate in again [8,10].…”
mentioning
confidence: 99%